Women's experiences of disrespect and abuse in Swiss facilities during the COVID-19 pandemic: a qualitative analysis of an open-ended question in the IMAgiNE EURO study - Alessia Abderhalden-Zellweger; Claire de Labrusse; Michael Gemperle; Susanne Grylka-Baeschlin; Anouck Pfund; Antonia N. Mueller; Ilaria Mariani; Emanuelle Pessa Valente; Marzia Lazzerini (BMC, 2024)
Abstract Background The COVID-19 pandemic has challenged the provision of maternal care. The IMAgiNE EURO study investigates the Quality of Maternal and Newborn Care during the pandemic in over 20 countries, including Switzerland. Aim This study aims to understand women's experiences of disrespect and abuse in Swiss health facilities during the COVID-19 pandemic. Methods Data were collected via an anonymous online survey on REDCap®. Women who gave birth between March 2020 and March 2022 and answered an open-ended question in the IMAgiNE EURO questionnaire were included in the study. A qualitative thematic analysis of the women's comments was conducted using the International Confederation of Midwives' RESPECT toolkit as a framework for analysis. Findings The data source for this study consisted of 199 comments provided by women in response to the open-ended question in the IMAgiNE EURO questionnaire. Analysis of these comments revealed clear patterns of disrespect and abuse in health facilities during the COVID-19 pandemic. These patterns include non-consensual care, with disregard for women's choices and birth preferences; undignified care, characterised by disrespectful attitudes and a lack of empathy from healthcare professionals; and feelings of abandonment and neglect, including denial of companionship during childbirth and separation from newborns. Insufficient organisational and human resources in health facilities were identified as contributing factors to disrespectful care. Empathic relationships with healthcare professionals were reported to be the cornerstone of positive experiences. Discussion Swiss healthcare facilities showed shortcomings related to disrespect and abuse in maternal care. The pandemic context may have brought new challenges that compromised certain aspects of respectful care. The COVID-19 crisis also acted as a magnifying glass, potentially revealing and exacerbating pre-existing gaps and structural weaknesses within the healthcare system, including understaffing. Conclusions These findings should guide advocacy efforts, urging policy makers and health facilities to allocate adequate resources to ensure respectful and high-quality maternal care during pandemics and beyond.